Substitution of manure for mineral P fertilizers increases P availability by enhancing microbial potential for organic P mineralization in greenhouse soil - Sun, Ruibo; Niu, Junfang; Luo, Bingbing; Wang, Xiaogai; Li, Wenyan; Zhang, Wenjie; Wang, Fenghua; Zhang, Chaochun; Ye, Xinxin (Frontiers in Bioengineering and Biotechnology, 2022)
The shortage of phosphorus (P) resource is a great challenge for the sustainable development of agriculture. Manure contains high amount of P and is a potential substitute for mineral P fertilizers. However, the effects of manure substitution for mineral P fertilizers on soil P availability and soil microbial P transformation is little known. In this study, the variations of soil P availability and bacterial P mobilization under the treatment with manure application instead of mineral P fertilizes application were evaluated. In the studied greenhouse fruit and vegetable production system, substitution manure for mineral P (PoR) maintained similar level of soil total P and fruit and vegetable yield as the traditional fertilization, but significantly increased the content of soil available P. In addition, PoR treatment enhanced bacterial organic P mineralization potential, while decreased inorganic P dissolution potential. These results demonstrated that manure application increased the availability of soil P primary through enhancing soil microbial Po mineralization and indicated the possibility of applying manure instead of mineral P fertilizers in greenhouse farming.